Biscutum constans coccolith size patterns across the mid Cretaceous in the western Tethys: Paleoecological implications - Bottini, Cinzia; Faucher, Giulia (Palaeogeography, Palaeoclimatology, Palaeoecology, 2020)
The morphometric record of the calcareous nannofossil species Biscutum constans from the western Tethys indicates that this species underwent marked size changes across the latest Barremian-Cenomanian interval (~ 28 Myrs). Significant size reduction occurred during the core of the early Aptian Oceanic Anoxic Event (OAE) 1a (~ 120 Ma) and soon after OAE 1a followed by a 9 Myr-long interval characterized by small specimens. Larger coccoliths marked the middle to late Albian and, particularly, the lower part of the nannofossil subzone NC10a was characterized by abundant large specimens. A minor size decrease coincided with the late Albian OAE 1d onset (~ 100 Ma), but very small size was reached again during the latest Cenomanian OAE 2 (~ 94.4 Ma). The sequence of relatively long (millions of years) intervals marked by different average sizes is interpreted to reflect adaptation to changing paleoecological conditions. Temperature and fertility were not directly influencing the size of B. constans. On shorter time scale, abrupt changes in ocean chemistry related to Large Igneous Provinces submarine volcanism played a central role in secretion of small B. constans coccoliths to face ocean acidification during OAE 1a and OAE 2. Contrarily, during the late early Aptian-early Albian time interval, smaller B. constans size was related to cooler temperature which possibly also promoted CO2 sequestration in cooler surface waters forcing B. constans to produce small coccoliths to survive lowered pH. In addition, pulses of subaerial volcanism of the Southern Kerguelen Plateau may have further affected the ocean chemistry. The termination of intense volcanism and warmer temperature in the middle Albian-early Cenomanian coincided with restoration of bigger B. constans specimens.